Workplace-Related Factors Associated With Employees' Standing Time at Work: A Research Brief. Issue 4 (May 2019) - Wilkerson, Amanda H.; Usdan, Stuart L.; Knowlden, Adam P.; Leeper, James L.; Birch, David A.; Hibberd, Elizabeth E.
Purpose: The purpose of this study was to identify the relationship between work-related, individual, and environmental factors and self-reported standing time during the workday. Design: Cross-sectional study design. Setting: Participants were recruited from a large, public university in the southeastern United States. Measures: Data were collected through an 87-item online survey using previously validated scales that assessed workplace standing time, demographic variables, work-related psychosocial factors, and workplace environment factors. Analysis: One-way analysis of variance, Pearson correlation coefficients, and nonparametric tests were used to determine univariate relationships between standing time and independent work-related variables and demographic factors. Results: Mean standing time among the sample (n = 502) was 72.49 minutes (standard deviation = 73.48) daily. There was a significant relationship between standing time and barrier self-efficacy for standing at work, self-regulation strategies, social norms, local connectivity in the workplace, overall connectivity in the workplace, and proximity of coworkers. Standing time was significantly higher for men, employees with an advanced degree, employees with a standing desk, and faculty. Conclusion: Health promotion researchers and practitioners should consider factors at multiple levels of influence when designing studies to explore workplace sedentary behavior. The findings regarding variations in workplace behavior by employee subgroups should be taken into consideration when designing future studies in the workplace.